Governance options for effective interprofessional education: Exposing the gap between education and healthcare services. (2nd October 2020) - O'Keefe, Maree; Forman, Dawn; Moran, Monica; Steketee, Carole
Abstract: Context: The increase in interprofessional models of collaborative practice and identification of health services as interprofessional organisations, sits somewhat awkwardly with traditional governance systems for both health services and educational institutions. Whereas health services have a primary focus on assuring competence and safety for health care practice, educational institutions have a primary focus on assuring academic standards within specific qualifications. Bridging the gap between these two systems with a workable option has proven challenging, especially in relation to interprofessional education (IPE). Objectives: Given the need to ensure 'work ready' graduates within a more interprofessional and collaborative workforce, it is important to review the quality assurance governance models that are in place and to consider which of these existing governance systems, if either, is the more appropriate model for enabling and supporting IPE. Methods: This paper describes current issues in relation to governance for quality assurance, summarises the current state of research in the field and discusses potential governance options moving forward. Conclusion: Given that existing governance models are not meeting the challenges of IPE, there is a need to achieve greater alignment between the academic and health service governing systems.